Performance analysis of combined transmit selection diversity and receive generalized selection combining in Rayleigh fading channels. - Xiaodong Cai (IEEE Transactions on wireless communications)
We analyze the average symbol error rate (SER) of M-PSK and M-QAM modulations with transmit antenna selection diversity (SD) and receive generalized selection combining (GSC) in Rayleigh fading channels. SER formulas are derived in closed form, and numerical results show that transmit SD and receive GSC are flexible to tradeoff performance for complexity.